6q24 Transient Neonatal Diabetes Mellitus-16 years of data collection. (24th May 2012) - Kabwama, S; Docherty, LE; Cook, E; Harrison, L; Ellard, S; Ennis, S; Shield, JPH; Mackay, DJG; Temple, IK
Abstract : Introduction: Transient Neonatal Diabetes Mellitus (TNDM) due to genetic aberrations at 6q24 is the commonest cause of diabetes presenting within the first week of life. It affects between 1:200, 000 and 1:400, 000 live births with the majority of infants born small for gestation age. TNDM predisposes to diabetes mellitus in later life. We report on the clinical presentation of the largest worldwide cohort of 6q24 TNDM cases. Results: 164 cases were analysed. The mean age of presentation was 8 days with a mode of 1 day and maximum age of presentation of 90 days. On average, babies recovered by 4.5 months with a mode of 2 months. Birth weight had a normal distribution with a median of 1987g and ranges from 3370g to 1050g. Most babies in the study were born at term and only 13 babies were born pre-term. 33.5% had paternally inherited duplications at 6q24, 29.3% had a maternal methylation mutation, and 37.2% had paternal UPD6. The data revealed a positive correlation between age of presentation and both birth weight and gestation (p=0.04 and p = 0.007 respectively)). No significant difference between the three genetic abnormalities (duplication, methylation and UPD6) in terms of age of presentation, remission, birth weight and gestation was observed. However, analysis of variance (ANOVA) identified a significant difference (p=0.016) between the three genetic abnormality groups in terms of birth weight corrected centile and this effect is most strongly observed when comparing babies carrying a methylation mutation against the other two groups combined (mean corrected centile 6.98 versus 1.91 respectively, p = 0.005). Conclusions: These results help define the clinical presentation of 6q24 TNDM. The data are consistent with larger babies having a later age of presentation-bigger babies may have some sub-optimal insulin secretory capacity hence the later age of presentation. The results also indicate that TNDM due to methylation mutations is associated with a bigger birth weight than that seen with other genetic causes.